Noble metal-doping of nanostructured tin(II) sulfide - Falkenbach, Oliver; Tinz, Jan; Schulze, Anne S.; Mueller, Eckhard; Schlecht, Sabine; et al. (physica status solidi (a), 2016)
Containing two environmentally friendly elements, tin monosulfide (SnS) is considered to be a possible candidate for sustainable thermoelectrics in the medium temperature range. Nanostructured SnS was synthesized via mechanical alloying and a solvothermal method. Two different ways for compacting of the nanopowders were applied, cold pressing and hot pressing, yielding similar results. A maximum ZT value of 0.075 at 773 K was obtained, independently from the preparation procedures. In order to improve the thermoelectric properties, mechanically alloyed SnS was doped with copper, silver, palladium, and platinum. Using silver as dopant, the efficiency could be doubled, while a tin substitution with the other elements did barely affect the thermoelectric transport. A comparison to single crystalline SnS reveals a reduced thermal conductivity through nanostructuring. The structure of the products was examined via X-ray diffraction (XRD) and transmission electron microscopy (TEM) showing a nanoscopic character with slightly varying lattice constants. In the case of larger sized impurity atoms secondary phases occur, indicating the solubility limits were reached and only partial incorporation of the added dopant amount into the matrix took place.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Ag; earth abundance; mechanical alloying; SnS; solvothermal method; sustainable materials; thermoelectrics